Community-Centered Policing Strategies for Enhancing Urban Public Security - Wachyono Wachyono (Jurnal Scientia Indonesia, 2025)
This study examines the effectiveness of community-centered policing strategies in enhancing urban public security. Rapid urbanization in developing countries increases social complexity and crime vulnerability, requiring adaptive policing models. The research aims to evaluate how community involvement, data-driven monitoring, and preventive patrol techniques contribute to public trust and safety outcomes. A mixed-methods approach was used, combining quantitative crime-rate analysis from 2015–2023 with qualitative interviews involving police officers, community leaders, and local residents. Results show that community-centered policing significantly reduces property crime by 18% and increases public reporting behavior by 27%. The integration of digital surveillance systems and neighborhood security forums further improves police responsiveness and social cohesion. The study concludes that strengthening partnerships between police institutions and urban citizens is essential to creating sustainable security ecosystems. Findings contribute to the scientific understanding of collaborative crime-prevention frameworks and offer practical policy recommendations for urban security reform.